Oral manifestations of a sinus melanoma: case report and literature review - Le Donne Mélanie; Bodard Anne-Gaëlle; Lesage Candice; Fleury Bertrand (EDP Sciences, 2019)
Introduction: Mucosal melanoma (MM) is a rare malignancy of the head and neck. Sinonasal melanomas are the most frequent, followed by oral melanomas. Observation: A 67-year-old patient with a known left sinus melanoma initially treated with immunotherapy was referred for consultation concerning mobile teeth. A pigmented lesion infiltrating the left maxillary arch in the molar area was detected. The malignancy had invaded the oral mucosa. Despite many proposed treatments (immunotherapy, chemotherapy, and radiotherapy), the patient showed metastatic progression, which resulted in death. Discussion: Sinus MMs are malignancies with poor prognosis because these are often diagnosed in the late stages of disease progression. As these tumors are rare, there is no treatment consensus and surgery remains the best option. Diagnosis of pigmented lesions of the oral mucosa is sometimes complicated because of various implied etiologies. Conclusion: This case report shows that sinus MMs can induce pigmentation in the oral mucosa. These are rare malignancies with poor prognosis, for which no treatment consensus exists to date.